Reflections on prescription and cancellation on the thirtieth anniversary of the Peruvian Civil Code - Ariano Deho, Eugenia (2014)
In the Peruvian Civil Code, there is a short Bookin which two fundamental legal institutionsare regulated: Prescription and cancellation of rights. A lot has been written and discussedabout them, from their judicial nature to theform in which they are legally drafted, sincetheir scope goes beyond the Civil Code.In the present article, the author presents some critical reflexions about certain topics related  to such institutions, to clarify  their application and understanding.